Implementation Of Policies To Manage The Impact Of Biological Agency Hazards On National Defense - Sitti Faridah; Ahmad Dohamid; Rudi Sutanto; Afifuddin; Sri Sundari (CV. AFDIFAL MAJU BERKAH, 2024)
At the outset of 2020, the Coronavirus Disease 2019 (Covid-19) outbreak originated in Wuhan, China, rapidly escalating into a global pandemic, reaching Indonesia. The ensuing confusion and panic prompted the Ministry of Defense to enact Policy Number 15 of 2015, addressing the mitigation of dangerous biological agent impacts on national defense. Employing a descriptive qualitative approach, this research examines factors influencing the implementation of this policy. The theoretical framework by MS Grindle, encompassing Policy Content and Policy Context Aspects, serves as a basis for analysis. Findings reveal suboptimal factors affecting policy implementation. Recommendations for improvement span both aspects. Regarding Policy Content, the study advocates for enhanced synchronization and coordination among pertinent Ministries/Government Agencies. It proposes the establishment of a National Coordinating Agency for Disease Outbreak Management (BNPWP) to spearhead prevention efforts. Additionally, the creation of guidelines for outbreak prevention and control due to biological threats is suggested. In terms of Policy Context, the research underscores the need for consistency with regulations and recommends prioritized strategies for effective threat prevention programs. Collaborative agreements through Memoranda of Understanding (MoUs) with relevant agencies are also encouraged. Stakeholders, including leaders from Ministries, TNI, Polri, and Regional Leaders, should actively participate in policymaking to avert confusion and overlaps. In conclusion, optimizing policies necessitates improved coordination, the establishment of a dedicated coordinating agency, and the development of comprehensive guidelines. Consistency with regulations, strategic prioritization, and stakeholder involvement are imperative for the effective implementation of policies safeguarding national defense against biological threats.